Object location and object recognition memory impairments, motivation deficits and depression in a model of Gulf War illness - Hattiangady, Bharathi; Mishra, Vikas; Kodali, Maheedhar; Shuai, Bing; Rao, Xiolan; Shetty, Ashok K. (Frontiers in Behavioral Neuroscience, 2014)
Memory and mood deficits are the enduring brain-related symptoms in Gulf War illness (GWI). Both animal model and epidemiological investigations have indicated that these impairments in a majority of GW veterans are linked to exposures to chemicals such as pyridostigmine bromide (PB, an anti nerve gas drug), permethrin (PM, an insecticide) and DEET (a mosquito repellant) encountered during the Persian Gulf War-1. Our previous study in a rat model has shown that combined exposures to low doses of GWI-related (GWIR) chemicals PB, PM and DEET with or without 5-minutes of restraint stress (a mild stress paradigm) causes hippocampus-dependent spatial memory dysfunction in a water maze test and increased depressive-like behavior in a forced swim test. In this study, using a larger cohort of rats exposed to GWIR-chemicals and stress, we investigated whether the memory deficiency identified earlier in a water maze test is reproducible with an alternative and stress free hippocampus-dependent memory test such as the object location test. We also ascertained the possible co-existence of hippocampus-independent memory dysfunction using a novel object recognition test, and alterations in mood function with additional tests for motivation and depression. Our results provide new evidence that exposure to low doses of GWIR-chemicals and stress for four weeks causes deficits in hippocampus-dependent object location memory and perirhinal cortex-dependent novel object recognition memory. An open field test performed prior to other behavioral analyses revealed that memory impairments were not associated with increased anxiety or deficits in general motor ability. However, behavioral tests for mood function such as a voluntary physical exercise paradigm and a novelty suppressed feeding test showed decreased motivation and depression. Thus, exposure to GWIR-chemicals and stress causes both hippocampus-dependent and hippocampus-independent memory impairments as well as mood dysfunction.